RESULTS OF THERMAL COMFORT EVALUATION WITH DIFFERENT CRITERIA - António Martins (2013)
In order to guarantee the reliability of the results, the methodology used along the recollection of data is not indifferent. This research work aims at verifying if, in closed spaces inside a paper plant, there are significant variations of the thermal environment due to the criteria variation of the gathering data. With this purpose in mind, measurements were made during a work shift in various places, and we arrived at the conclusion that even in apparently stable atmospheres there may be significant variations in thermal comfort.